Health problems in youth competitive alpine skiing: A 12-month observation of 155 athletes around the growth spurt - Schoeb, T.; Peterhans, L.; Fröhlich, S.; Frey, W. O.; Gerber, C.; Spörri, J. (Scandinavian Journal of Medicine & Science in Sports, 2020)
Alpine ski racing is known as a high-risk sport; however, little is known on the health problems occurring at youth level. The purpose of this study was to investigate the prevalence of health problems in youth competitive alpine skiers with respect to sex, age, and season differences, to describe their severity and location and to assess the influence of biological maturation. Over a 12-month period, 155 youth competitive alpine skiers around the growth spurt were prospectively monitored for health problems using the Oslo Sports Trauma Research Centre (OSTRC) questionnaire. These data were verified by supplemental interviews at the end. Biological maturation was estimated by a non-invasive, anthropometric-based assessment method. During competition season, 42.2% of the skiers suffered from health problems and 19.8% reported their problem being substantial. Females had significantly higher rates of acute and overuse injuries compared to males, while there was no sex difference in duration, severity, and time loss. Skiers of the category U15 showed higher prevalence of acute and overuse injuries than U14 skiers. During preparation season, health problem prevalence was substantially lower. The knee was found to be the most affected body part for both acute and overuse injuries. There was a direct association between the offset to the age at peak height velocity (APHV) and the occurrence and severity of acute injuries. In conclusion, youth competitive alpine skiers suffer from a large number of health problems. Since sex, age, and biological maturation are important, effective injury prevention should already start before reaching the APHV.